PENERAPAN MEDIA GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR IPA PADA SISWA KELAS VI SDN 011 SUNGAI SALAK - Nurhayati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Media is a connecting tool that can connect or communicate. Therefore, media is an important thing to ease the teaching and learning process. Media is also a tool to provide students’ interest. Picture media plays an important role in the teaching and learning process, messages are conveyed through pictures to the sense of sight. Picture is a learning tool to deliver the teaching and learning material from the teacher to students in order to ease students comprehend the learning materials, remember the contents of the learning material explained by the teacher, increase the students’ insight, help students’ interest in participating in learning activity, and facilitate their activities during teaching and learning process. Hence, this article discusses the implementation of pictures to increase natural science learning outcomes. The research explained in this article uses Classroom Action Research (CAR) with a research design model of Kemmis and Mc. Taggart. It was conducted at SDN 011 Sungai Salak. The research subjects involved 20 students, 11 male and 9 female students. Learning outcomes obtained from the pre-cycle, cycle I, and cycle II showed the improvement. During the first cycle, the average value obtained was 75.25 and classical completeness percentage was 75% higher than pre-cycle classical completeness. Whilst in the second cycle it showed an average score of 85.50 and classical completeness percentage of 90%. In this occasion, it could be said that it was achieved the objective of picture media use in improving students’ learning outcomes at SDN 011 Sungai Salak.